Antioxidant Activity of Rumex conglomeratus P. Collected from Turkey - Kilic1, Ismail; Yesiloglu, Yesim; Bayrak, Yuksel; Gulen, Sezer; Bakkal, Tahir (Asian Journal of Chemistry, 2013)
Plants contain a wide variety of free radical scavenging molecules, such as flavonoids, anthocyanins, carotenoids, dietary glutathionine, vitamins and endogenous metabolites and such natural products are rich in antioxidant activities. Rumex conglomeratus P. is widely spread in Turkey and used as an anticonstipate in traditional medicine. In this study, the antioxidant activity of water extract of R. conglomeratus was evaluated using different antioxidant tests. In addition, carotenoid content and proline level of R. conglomeratus were also determined. The results were compared with natural and synthetic antioxidants. The results showed that R. conglomeratus contained naturally occuring antioxidant components and possessed antioxidant activity which may be attributed to its radical scavenging and metal chelating activities. It was concluded that R. conglomeratus might be a potential source of antioxidants.